Caracterização sociodemográfica, clínica, psicossocial e espiritual de pacientes renais crônicos - Ferreira, Leny Gonçalves (2017)
Chronic Kidney Disease (CKD) as well as its related treatments present significant impacts to the patients, family, and the entire health system as research has been showing. More specific intervention programs can be provided from a more effective knowledge of thisassisted population. Objectives: To identify and characterize the biopsychosocial and spiritual profile including sociodemographic and clinical data, anxiety and depression symptoms, quality of life, coping strategies and issues related to spirituality, religion and / or personal beliefs. Materials and Methods: Descriptive exploratory study with patients of both genders, agedover 18, with chronic renal failure – CRF, undergoing renal replacement therapy (hemodialysis, peritoneal dialysis and renal transplantation); attended at a school hospital in the interior of the State of São Paulo. After the patients´ agreement and their signingto the Informed Consent Term (ICT), they answered an individual interview with an Identification Card, Hospital Scale of Anxiety and Depression - HAD, WHOQOL-bref - quality of life, Scale of Modes of Coping Problems - EMEP and WHOQOL - spirituality, religiosity and personal beliefs - SRPB. Data were analyzed and grouped by frequency and percentage of answers, and discussed from the literature related to the area. Results: A total of 174 patients, predominantly between 41 and 70 years old (70.69%), 53.45% male, and 47.70% with incomplete primary education participated; as baseline disease, Systemic Arterial Hypertension (36.21%) and Diabetes Mellitus (25.29%) were found among others; major comorbidities Systemic Arterial Hypertension (47.70%) and Diabetes Mellitus (29.31%). Clinical symptoms of anxiety were presented in 70.11%, and 75.29% had depression. According to the quality of life, results were slightly above average, considering the analogue scale of the instrument. Regarding coping strategies, the highest averages were for Focus on Emotion, followed by Focus on the Problem and Social Support. Regarding issues related to spirituality, religion and / or personal beliefs, the best-rated facet was 'Faith', followed by 'Sense in the Life”. Conclusions: Sociodemographic data, quality of life, coping strategies, and religiosity / spirituality are according to the literature reports. However, clinical symptoms of anxiety and depression were significantly higher than those found in the general population and for chronic kidney patients. These findings have pointed out the need for specific intervention programs toward this sample evaluated, as well as further research in the area.